Understanding pre-emotion and post accident analysis by using valence arousal - Abdul Rahman, Abdul Wahab; Abdul Majid, Hariyati Shahrima (s.n, 2012)
Driver behavior is indeed reckoned to be one of the highest factors affecting fatal accidents. However, majority of the cases can be avoided if the driver can remain focus and make a correct decision in controlling the vehicle while driving. Decision-making ability of the driver is impeded due to driver behavior which may involve precursor emotion of the driver that could lead to fatal accident. Thus, understanding and analyzing the driver behavior and the resulting emotion can help prevent accident and reducing accident fatality rate. In this thesis, the correlation between precursor emotions to pre-post accidents using driving simulator is studied in details.